Ylioppilastutkinnon muotoutuminen autonomian aikana - Lindström, Aslak (1998)
In all so-called developed countries there is a school leaving examination at the end of secondary education. School leaving examinations in different countries have similar aims but differ in form and in their emphasis on various tasks. This research looks at the development of the Matriculation Examination in the period of autonomy in Finland. The study was carried out using historical research methods. The most important sources of information were: parliamentary records, the National Board of Education, teachers' meetings, the central archives of the University of Helsinki and the National Archives, committee reports and other relevant research. The aim was to clarify how various aspects of Finnish society are connected with the position and development of the Matriculation Examination. Factors considered included: cultural bilingualism, the development of Western thought and learning, the transition from the Assembly of Representatives of the Estates to Parliament, social and economic changes, the politics of Russification, the opening of education to women, changes in the education system, and the separation of Church and school. The tasks set in the Matriculation Examination were also studied. The roots of the Finnish Matriculation Examination in the period of autonomy are to be found in Fennomania, the emancipation of women, and factors related to educational equality. Finland was the first Nordic country to stress the significance of the Matriculation Examination in national development. Bilingualism led to difficulties between cultural groups which, in tum, hindered development. The politics of Russification slowed the process of reform. However, it was only in independent Finland that extensive changes were made to the examination. The Assembly of Representatives of the Estates emphasised the development of the Matriculation Examination at the expense of elementary schooling. The birth of the political party system diverted attention towards educating the population. Improved attitudes towards learning and openness to new ideas led to an increase in the number of people passing the Matriculation Examination. There was a time lag between changes in the education system and subsequent changes in the examination. The Matriculation Examination had a central significance for women's equality when university studies became open to them. Written tests were transferred from universities to upper secondary schools in 1874, and oral examinations in 1919. Nevertheless, the universities continued to influence the examination after 1919. The aims for the examination, set by society as a whole, were as follows: 1) realising political objectives, 2) legitimising educational reform. 3) implementing equality in education 4) developing the curriculum, 5) developing teaching and teaching methods, 6) selecting students for universities, 7) organising educational provision, and 8) granting educational status. Reform of the examination after independence was made possible by innovators in key administrative positions. It was also helped by the fact that classical education was given a lower priority. Growth in the number of upper secondary school leavers soon meant that the examinations could no longer be sat in universities. The Matriculation Examination develops along with many features of Finnish society. It appears that the examination can be modified only in accordance with social change. The aims of the examination must be carefully considered when making amendments.